An electronically switchable leaky wave antenna. - Limin Huang
We report an electronically switchable dielectric leaky wave antenna. The main beam angle can be electronically steered using p-i-n diodes. The diodes are used as switches to control the radiation from two sets of gratings with different periods, thereby switching the main beam angle. Beam steering is achieved at a single fixed frequency; no frequency sweeping is necessary. A microwave prototype demonstrates a 35° change in beam direction at 3.5 GHz. Measured antenna patterns agree with theoretical predictions. This approach should be scalable to millimeter-wave frequencies using diodes monolithically integrated on a semiconductor waveguide
Keywords: 3.5 GHz; SHF; Beam direction; Beam steering; Dielectric leaky wave antenna; Dielectric loaded antennas; Electronically steered antenna; Electronically switchable leaky wave antenna; Fixed frequency; Gratings; Main beam angle; Main beam angle switching; Measured antenna patterns; Microwave prototype; Millimeter-wave frequencies; Monolithically integrated diodes; P-i-n diodes; Periods; Radiation; Semiconductor waveguide